Preparation method and application of peroxidase-like activity and acoustic-thermal effect dual-response composite hydrogel

By designing a double-response composite hydrogel with peroxidase-like activity and acoustothermal effect, PDA@MoS2 is used to catalyze H2O2 under ultrasound, the inflammatory response problem caused by excessive H2O2 level at the wound is solved, and the effect of accelerating wound healing and improving antibacterial efficiency is achieved.

CN119970621APending Publication Date: 2025-05-13FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510159111.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-05-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the H2O2 level at the wound, resulting in enhanced wound inflammatory response and delayed healing.

Method used

A peroxidase-like activity and acoustothermal effect double-response composite hydrogel was designed to catalyze the conversion of H2O2 to·OH under ultrasound by loading PDA surface-modified MoS2 (PDA@MoS2) to catalyze the conversion of H2O2 to·OH under ultrasound, reducing inflammation levels and improving antibacterial efficiency.

Benefits of technology

The dual anti-inflammatory effect is achieved, accelerates the process of inflammation regression and wound healing, and significantly improves the antibacterial efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method and application of peroxidase-like activity and acoustic-thermal effect dual-response composite hydrogel. The hydrogel is mainly prepared from polydopamine (PDA), molybdenum disulfide (MoS2), oxidized konjac glucomannan (OKGM) and carboxymethyl chitosan (CMCs). The hydrogel catalyzes H2O2 to be converted into. OH through PDA-loaded surface modified MoS2 (PDA-coated MoS2), meanwhile, ultrasonic waves are used for increasing the temperature of a wound and exciting the activity of normal immune cells, the hydrogen peroxide (H2O2) level of the wound is reduced through the synergistic effect of the PDA-loaded surface modified MoS2 and the ultrasonic waves, the inflammatory reaction is improved, and wound healing is promoted. The hydrogel prepared by the invention is low in cost, simple and convenient in preparation method and good in biocompatibility, has peroxidase-like activity, acoustic-thermal dual response and excellent heat preservation capability, and has strong application potential in the field of treatment of inflammatory wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biomedical materials, and in particular to a preparation method and application of a peroxidase-like activity and acoustic-thermal effect dual-responsive composite hydrogel. Background Art

[0002] Wound healing is a highly complex pathophysiological response to injury, including four stages: hemostasis, inflammation, proliferation, and remodeling, which overlap in time and space. Inflammation is an integral part of the wound healing stage, and its purpose is to remove dead cells and potential pathogens from the wound. When inflammation occurs in the wound, leukocytes and macrophages are attracted to the wound through chemotaxis to remove dead cells and bacteria from the wound. Once the pathogens and dead cells disappear from the wound, leukocytes undergo apoptosis to prevent further tissue damage or aggravate inflammation. The remaining macrophages release various growth factors to activate the surrounding keratinocytes, fibroblasts, and endothelial cells, allowing the wound to heal slowly. If leukocytes do not undergo apoptosis when cleaning the wound, the process of the wound entering the proliferation phase will be delayed or inhibited. Through the stimulation of proinflammatory factors, the wound remains in an inflammatory cycle that is difficult to break, so the occurrence and resolution of the inflammatory response is the primary condition for wound healing and a key factor in determining the quality and duration of wound healing.

[0003] H2O2 is a strong oxidizing substance that plays an important role in many physiological processes such as cell growth, immune response and aging. At the same time, the imbalance of H2O2 production is closely related to diseases such as cancer, diabetes and inflammation. In wounds, moderate H2O2 can act as a secondary messenger for cell signal transduction, and plays an important role in the production of various growth factors and the migration of epidermal cells. Excessive H2O2 can trigger wound inflammation and prevent the formation of connective tissue, making it difficult for wounds to heal. Therefore, reducing the level of H2O2 at the wound can accelerate wound healing, which provides a new solution for wound treatment. Berwin Singh et al. designed a polyoxide nanoparticle (PVAX) containing vanillyl alcohol (VA). The VA in the nanoparticle can react specifically with H2O2, thereby reducing the level of H2O2 at the site of application. In in vivo experiments, a certain amount of PVAX was shown to have a healing effect on the excisional wounds of mice, significantly accelerating the healing process, reducing wound size, and accompanied by re-epithelialization and collagen deposition, providing a new therapeutic strategy for wound treatment (Roy S, Khanna S, Sen CK. Redox regulation of the VEGF signaling path and tissue vascularization: Hydrog enperoxide, the common link between physical exercise and cutaneous wound healing [J]. Free Radical Biology and Medicine, 2008, 44 (2): 180-192.).

[0004] The level of H2O2 in organisms is mainly regulated by various enzymes in cells, such as peroxidase (POD), catalase (CAT), superoxide dismutase (SOD), glucose oxidase (GOx) and glutathione peroxidase (GPx). Although these natural proteases have excellent catalytic activity and substrate selectivity, their high cost, unadjustable catalytic reaction and poor stability limit their further application. Artificially synthesized nanozymes have become a hot topic of research in recent years due to their low cost, flexible design and high stability. As a typical POD-like active nanozyme, MoS2 plays an important role in the field of catalysis of H2O2, but the shortcomings of MoS2 such as poor dispersibility in water and low catalytic activity limit its wide application in the biomedical field. Studies have shown that enhancing the dispersibility of MoS2 in water will help improve its POD-like activity, biocompatibility, catalytic speed and substrate selectivity, which provides a new design idea for MoS2 in the biomedical field, especially for the treatment of slow wound healing caused by H2O2 abnormalities.

[0005] Based on the above research, a dual-responsive composite hydrogel with peroxidase-like activity and acoustic thermal effect was designed, which has great application potential in the field of wound treatment. Summary of the invention

[0006] In view of the existing problems, the present invention designs a composite hydrogel with peroxidase-like activity and acoustic thermal effect dual response based on the characteristics of POD-like active nanozymes and ultrasonic response characteristics. The hydrogel is mainly composed of polydopamine (PDA), molybdenum disulfide (MoS2), oxidized konjac gum (OKGM) and carboxymethyl chitosan (CMCs). By loading PDA surface-modified MoS2 (PDA@MoS2), catalyzing H2O2 to be converted into OH, significantly reducing the level of inflammation and improving antibacterial efficiency. At the same time, the introduction of ultrasound not only increases the local temperature of the wound, but also further activates the POD activity of PDA@MoS2 through its mechanical effect and cavitation effect, thereby achieving a dual anti-inflammatory effect, accelerating the disappearance of inflammation and improving antibacterial efficiency.

[0007] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a composite hydrogel with dual response of peroxidase-like activity and acoustic-thermal effect comprises the following steps: (1) Na2MoO4·2H2O and L-cys were dissolved in 50 mL of deionized water, and the mixture was stirred under magnetic stirring at room temperature for 2 h. The mixed solution was transferred into a polytetrafluoroethylene liner and reacted at 180°C for 24 h. The obtained product was centrifuged, washed, vacuum dried, and then ground to obtain MoS2 powder. (2) MoS2 powder was dispersed in 50 mL of deionized water, the pH was adjusted to 8.8 with 2 M NaOH solution, DA was added, and the reaction was carried out under magnetic stirring at room temperature for 2 h. The obtained product was centrifuged and washed, vacuum dried and then ground to obtain PDA@MoS2; (3) KGM was dissolved in 100 mL of ultrapure water, 10 mL of NaIO4 aqueous solution was added thereto, and the mixture was reacted for 12 h under magnetic stirring at room temperature in the dark, and then 10 mL of ethylene glycol was added to quench the excess NaIO4. After stirring for 2 h, the mixed solution was dialyzed in ultrapure water for 3 days, centrifuged, and the supernatant was freeze-dried to obtain OKGM; (4) 0.5 mL of OKGM aqueous solution was placed in a centrifuge tube, PDA@MoS2 was added thereto and mixed thoroughly, and then 0.5 mL of CMCs aqueous solution was added and stirred rapidly at room temperature until a gel was formed to obtain PDA@MoS2@Gel hydrogel, which is a dual-responsive composite hydrogel with peroxidase-like activity and acoustic thermal effect.

[0008] In the above step (1), the amounts of Na2MoO4·2H2O and L-cys used are 0.348 g and 0.454 g, respectively.

[0009] In the above step (2), the amounts of MoS2 and DA used are 200 mg and 500 mg respectively.

[0010] In the above step (3), the amount of KGM used is 1 g and the concentration of the NaIO4 aqueous solution is 10 wt%.

[0011] In the above step (4), the concentrations of the CMCs aqueous solution and the OKGM aqueous solution are 9wt% and 6wt% respectively, and the amount of PDA@MoS2 used is 1mg.

[0012] A composite hydrogel with dual response of peroxidase-like activity and acoustic-thermal effect prepared by the above preparation method.

[0013] The above-mentioned peroxidase-like activity and acoustic-thermal effect dual-responsive composite hydrogel is used in the preparation of drugs with antibacterial uses.

[0014] The above-mentioned peroxidase-like activity and acoustic thermal effect dual-responsive composite hydrogel is used in the preparation of drugs that promote wound healing.

[0015] The significant advantages of the present invention are: (1)PDA@MoS2@Gel hydrogel has good biocompatibility, ensuring the safe application of the hydrogel in wound sites.

[0016] (2) The acoustic thermal effect of ultrasound combined with the heat preservation ability of PDA@MoS2@Gel hydrogel provides a warm microenvironment for the wound that is conducive to tissue repair, accelerates cell proliferation and migration, and promotes the wound healing process.

[0017] (3) The introduction of ultrasound not only increased the local temperature of the wound, but also further activated the POD activity of PDA@MoS2 through its mechanical effect and cavitation effect, thus achieving the dual anti-inflammatory effect of PDA@MoS2@Gel hydrogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 These are the XRD spectra and FT-IR spectra of MoS2 and PDA@MoS2.

[0019] Figure 2 These are the XPS spectra of MoS2 and PDA@MoS2.

[0020] Figure 3 (a) Zeta potential and (b) particle size diagram of MoS2 and PDA@MoS2.

[0021] Figure 4 It is the POD-like activity of PDA@MoS2.

[0022] Figure 5 This is a digital picture of the gelation process of PDA@MoS2@Gel hydrogel.

[0023] Figure 6 is the swelling rate and degradation rate of PDA@MoS2@Gel hydrogel.

[0024] Figure 7 It is the rheological property of PDA@MoS2@Gel hydrogel.

[0025] Figure 8 It is the POD-like activity of PDA@MoS2@Gel hydrogel.

[0026] Fig. 9 This is the acoustic thermal effect of PDA@MoS2@Gel hydrogel. (a) Infrared thermal imaging of heating, (b) Infrared thermal imaging of cooling.

[0027] Fig.10 The antibacterial properties of PDA@MoS2@Gel hydrogel.

[0028] Fig.11 This is the treatment result of PDA@MoS2@Gel on the rat full-thickness skin infection wound model. DETAILED DESCRIPTION

[0029] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0030] Embodiment 1: Step 1: Dissolve 0.348 g Na2MoO4·2H2O and 0.454 g L-cysteine ​​(L-cys) in 50 mL deionized water, react under magnetic stirring at room temperature for 2 h, then transfer the mixed solution into a polytetrafluoroethylene liner, react at 180 ° C for 24 h, centrifuge and wash the product obtained by the reaction with distilled water, dry it in a vacuum drying oven (60 ° C) for 8 h, and then grind it to a particle size of less than 400 nm to obtain MoS2 powder.

[0031] Step 2: Disperse 200 mg of MoS2 powder in 50 mL of deionized water, adjust the pH to 8.8 with 2 M NaOH solution, add 500 mg of dopamine (DA), and react with magnetic stirring at room temperature for 2 h. Wash the product by centrifugation with anhydrous ethanol, dry it in a vacuum drying oven (60°C) for 8 h, and then grind it to a particle size of less than 600 nm to obtain PDA@MoS2.

[0032] Step 3: 1g konjac gum (KGM) is dissolved in 100mL ultrapure water, 10mL NaIO4 aqueous solution is added thereto at a concentration of 10wt%, and after magnetic stirring and luminescence reaction for 12h at room temperature, 10mL ethylene glycol is added to quench excessive NaIO4, and after continuing to stir for 2h, the mixed solution is transferred to a dialysis bag with a molecular weight cut-off of 8000 to 14000, dialyzed with ultrapure water for 3 days, centrifuged after the dialysis is completed, and the supernatant is freeze-dried to obtain oxidized konjac gum (OKGM).

[0033] Step 4: Carboxymethyl chitosan (CMCs) and OKGM were prepared into aqueous solutions with concentrations of 6wt% and 9wt%, respectively; 0.5mL of 6wt% OKGM aqueous solution was placed in a centrifuge tube, 1mg PDA@MoS2 was added thereto and mixed thoroughly, and then 0.5mL of 9wt% CMCs aqueous solution was added and stirred rapidly at room temperature until a gel was formed to obtain PDA@MoS2@Gel hydrogel.

[0034] Figure 1 (a) XRD spectra and (b) FT-IR spectra of MoS2 and PDA@MoS2. Figure 1 It can be seen from Figure 1 that the diffraction peaks of the XRD patterns of MoS2 and PDA@MoS2 are basically the same, with obvious diffraction peaks at 33°, 34°, 58° and 60.5°, representing the (101), (012), (110) and (113) crystal planes of the MoS2 phase, respectively, indicating that the modification treatment of PDA did not change the crystal structure of MoS2. Figure 1 b It can be seen that the absorption peaks of the FT-IR images of MoS2 and PDA@MoS2 are basically the same, but the absorption peak of PDA@MoS2 at 3000cm -1 and 1620cm -1 New characteristic peaks appeared at the locations, which originated from the vibration of CH on the benzene ring and the ketone in PDA, indicating the successful preparation of surface PDA@MoS2.

[0035] Figure 2 The XPS graphs of MoS2 and PDA@MoS2 show that the total spectra of MoS2 and PDA@MoS2 contain four chemical elements: C, O, S, and Mo ( Figure 2 a). In the C1s spectrum ( Figure 2 b), PDA@MoS2 has two new peaks at 286.8eV and 288.9eV, which belong to CO and C=O respectively, and the CC characteristic peak originally at 284.9eV has a blue shift compared with MoS2, indicating that the chemical environment of C has changed. Figure 2c), PDA@MoS2 has a new characteristic peak at 533.6eV, which is attributed to C=O, and the original characteristic peak at 532.3eV has a blue shift, indicating that the chemical environment of O has changed. Figure 2 d), MoS2 has two characteristic peaks at 161.7eV and 163.1eV, which are blue-shifted in PDA@MoS2, which means that the chemical environment of S in PDA@MoS2 has changed. Figure 2 e), the peaks of MoS2 at 228.9eV and 231.2eV are respectively attributed to Mo 4+ 3d5 / 2 and Mo 4+ 3d3 / 2, the peak at 226.2eV belongs to S 2s, and these three peaks are blue-shifted in PDA@MoS2, indicating that the chemical environment of Mo has changed. The above results indicate the successful preparation of MoS2 and the successful loading of PDA.

[0036] Figure 3 (a) Zeta potential and (b) particle size of MoS2 and PDA@MoS2. Figure 3 It can be seen from a that compared with the Zeta potential of MoS2, the Zeta potential of PDA@MoS2 increases, which may be because the positively charged amino groups in PDA neutralize part of the negative charge of MoS2, thus leading to the increase in potential. Figure 3 b It can be seen that the particle size of PDA@MoS2 has increased compared with MoS2, which further proves the successful loading of PDA.

[0037] Figure 4 The POD-like activity of PDA@MoS2 was detected and analyzed by coumarin. The fluorescence intensity of low-concentration H2O2 was very low, indicating that almost no ·OH was produced. When PDA@MoS2 was co-incubated with 10mM H2O2, the fluorescence intensity increased rapidly within 6h, indicating that more ·OH was produced. The above results show that PDA@MoS2 has POD-like activity and can catalyze low-concentration H2O2 to produce ·OH.

[0038] Figure 5 This is a digital picture of the gelation process of PDA@MoS2@Gel hydrogel, proving that the polymer chains are cross-linked to form PDA@MoS2@Gel hydrogel.

[0039] Figure 6 The swelling rate and degradation rate of PDA@MoS2@Gel hydrogel are shown in Figure 2. It is proved that PDA@MoS2@Gel hydrogel has a lower swelling rate and a higher degradation rate.

[0040] Figure 7Rheology of PDA@MoS2@Gel hydrogel. It proves that PDA@MoS2@Gel hydrogel is injectable and self-healing.

[0041] Figure 8 The POD-like activity and acoustic thermal effect of PDA@MoS2@Gel hydrogel. PDA@MoS2@Gel hydrogel has POD-like activity. In the PDA@MoS2@Gel hydrogel + 10mM H2O2 system, compared with the PDA@MoS2@Gel hydrogel without ultrasonic treatment, after ultrasonic treatment (5min, 1MHz, 2.5W / cm 2 ) treated PDA@MoS2@Gel hydrogel can produce more ·OH, proving that PDA@MoS2@Gel hydrogel has acoustic thermal effect.

[0042] Fig. 9 This is the infrared thermal imaging image of PDA@MoS2@Gel hydrogel. Ultrasound (frequency 1 MHz, power density 2.5 W / cm 2 ) after 5 minutes of treatment, the temperature of the hydrogel increased from 14.3℃ to 44.0℃, and then dropped from 44.0℃ to 28.6℃ after 5 minutes of natural cooling, which proved that PDA@MoS2@Gel hydrogel has good thermal insulation ability.

[0043] Embodiment 2: Carboxymethyl chitosan (CMCs) was prepared into a 9 wt % aqueous solution, which was rapidly stirred at room temperature until a gel was formed to obtain a hydrogel, which was recorded as Hydrogel.

[0044] The antibacterial properties of PDA@MoS2@Gel hydrogel against Escherichia coli (E.coli) and Staphylococcus aureus (S.aureu) under different conditions were investigated by plate counting method. The specific steps are as follows: the hydrogel is prepared into a 10mm hydrogel disc, and then 4mL phosphate buffer (PBS) and 1mL of a certain concentration of bacterial suspension are added to the six-well culture plate, and finally the prepared hydrogel disc is placed in the six-well culture plate, 10mM H2O2 is added to mix it with the bacterial suspension, and co-cultured in the bacterial incubator for 12h. After the culture is completed, 100μL of the mixed solution is taken out and evenly coated on the bacterial culture plate, and then the culture is continued on the culture plate for 24h, and the number of bacterial colonies and their growth conditions are recorded by taking pictures. PBS is used as a blank control (Blank).

[0045] Fig.10The antibacterial properties of PDA@MoS2@Gel hydrogel. When the hydrogel was used alone to culture bacteria, the antibacterial rates of PDA@MoS2@Gel hydrogel were 20.3% (E. coli) and 8.3% (S. aureu), while when PDA@MoS2@Gel hydrogel was combined with 10mM H2O2, the antibacterial rates were 97.6% (E. coli) and 93.1% (S. aureu), indicating that PDA@MoS2@Gel hydrogel has great potential for application in wound infection.

[0046] Embodiment 3: After 24 hours of fasting and water deprivation, the rats were anesthetized by intraperitoneal injection of sodium pentobarbital solution. The hair on the back of the rats was then shaved and fully disinfected with alcohol. A skin punch with a diameter of 7 mm was used to accurately create full-thickness circular wounds on the symmetrical positions on both sides of the rats' backs. The diameter of each wound was also 7 mm. Subsequently, 100 μL of 1×10 8 CFU / mL of methicillin-resistant Staphylococcus aureus (MRSA) liquid was used to simulate the infection environment. During the treatment phase, four different treatment methods were used, namely normal saline, 3M wound dressing, blank hydrogel without drug loading, and special hydrogel for the experimental group. In addition to the corresponding treatment, the left wound of the rat was also subjected to ultrasound treatment at room temperature for 5 minutes (1MHz, 2.5W / cm 2 ); the wound on the right side maintained the original treatment method. After the model was successfully constructed, the healing progress of the rat wound was closely observed at different time points, and the wound status was recorded in detail using a digital camera. At the same time, according to the requirements of the treatment plan, the 3M dressing and hydrogel samples were regularly replaced, and ultrasound treatment was continued on the left wound.

[0047] Fig.11 These are the treatment results of a rat full-thickness skin infection wound model. Fig.11 a is a digital photo of wound healing at different times. Fig.11 b is the wound healing rate at different times. The wound area of ​​each group was reduced and basically healed on the 11th day ( Fig.11 a). Quantified wound healing diagram shows ( Fig.11b), the wound healing rate of the ultrasound-treated group was slightly higher than that of the non-ultrasonicated group. This is because the mechanical effect of ultrasound can promote the exchange of substances between cells and accelerate cell growth, which has a positive effect on wound healing. Among all the groups, the wound healing rate of PDA@MoS2@Gel hydrogel was the highest, reaching 77.3% (US-) and 80.0% (US+) on the 6th day, and 87.5% (US-) and 90.2% (US+) on the 8th day, which was much higher than that of other groups, indicating that PDA@MoS2@Gel hydrogel has a good ability to promote wound healing in the treatment of common wounds.

[0048] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a composite hydrogel with dual response of peroxidase-like activity and acoustic thermal effect, characterized in that: The following steps are involved: (1) Na2MoO4·2H2O and L-cys were dissolved in 50 mL of deionized water, and reacted under magnetic stirring at room temperature for 2 h. The mixed solution was transferred into a polytetrafluoroethylene liner and reacted at 180 °C for 24 h. The obtained product was centrifuged, washed, vacuum dried, and ground to obtain MoS2 powder. (2) MoS2 powder was dispersed in 50 mL of deionized water, the pH was adjusted to 8.8 with 2 M NaOH solution, DA was added, and the mixture was reacted under magnetic stirring at room temperature for 2 h. The obtained product was centrifuged and washed, vacuum dried, and then ground to obtain PDA@MoS2; (3) KGM was dissolved in 100 mL of ultrapure water, and 10 mL of NaIO4 aqueous solution was added thereto. After reacting for 12 h at room temperature under magnetic stirring in the dark, 10 mL of ethylene glycol was added to quench the excess NaIO4. After stirring for 2 h, the mixed solution was dialyzed in ultrapure water for 3 days, centrifuged, and the supernatant was freeze-dried to obtain OKGM. (4) Place 0.5 mL of OKGM aqueous solution in a centrifuge tube, add PDA@MoS2 and mix thoroughly, then add 0.5 mL of CMCs aqueous solution and stir rapidly at room temperature until a gel is formed to obtain PDA@MoS2@Gel hydrogel, which is a dual-responsive composite hydrogel with peroxidase-like activity and acoustic thermal effect.

2. The preparation method according to claim 1, characterized in that: In step (1), the amounts of Na2MoO4·2H2O and L-cys used are 0.348 g and 0.454 g, respectively.

3. The preparation method according to claim 1, characterized in that: In step (2), the amounts of MoS2 and DA used are 200 mg and 500 mg, respectively.

4. The preparation method according to claim 1, characterized in that: In step (3), the amount of KGM used is 1 g, and the concentration of the NaIO4 aqueous solution is 10 wt %.

5. The preparation method according to claim 1, characterized in that: In step (4), the concentrations of CMCs aqueous solution and OKGM aqueous solution are 9wt% and 6wt%, respectively, and the amount of PDA@MoS2 used is 1mg.

6. A composite hydrogel with dual response of peroxidase-like activity and acoustic thermal effect prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the composite hydrogel with dual response of peroxidase-like activity and acoustic thermal effect as claimed in claim 6 in the preparation of drugs with antibacterial uses.

8. Use of the composite hydrogel with dual response of peroxidase-like activity and acoustic thermal effect as claimed in claim 6 in the preparation of drugs for promoting wound healing.